Feasibility Study of Evening Gowns Through an Exploration of Layering Techniques - Talitha Zada Achmad; Irmayanti Irmayanti (Universitas Negeri Semarang, 2026)
This study aims to test the feasibility of an evening party dress design that explores layering techniques. This research applies a project-based design approach through the development of PPE (Planning, Production, and Evaluation). Product feasibility evaluation involved 3 expert panelists and 10 trained panelists using questionnaire instruments in the form of quantitative descriptive analysis sheets with percentages. The results of the due diligence showed that this evening party dress earned an overall average score of 95%, which placed it in the